PERSONAL RESOURCES, JOB RESOURCES, WORK ENGAGEMENT, PSYCHOLOGICAL EMPOWERMENT AND JOB SATISFACTION: A CONDITIONAL PROCESS ANALYSIS - Mabekoje, Sesan; Bamgbose, Abel O.; Azeez, Razaq O.; Okunuga, Olusola O.; Osoba, Adeniyi O. (African Journal of Behavioural and Scale Development Research, 2024)
Purpose: Studies are extensive on job satisfaction and especially as related with psychological empowerment. However, the mediation effect of work engagement in their relationship and as moderated by personal and job resources, is not well supported by the available data. This study examined the conditional process of the moderating roles of personal resources and job resources in mediating the effect of work engagement between psychological empowerment and job satisfaction. Method: Using a descriptive survey research design, 510 teachers selected through a multi-stage process among teachers in the Ogun East Senatorial District, Nigeria took part in the study. Five instruments were used for data collection with analysis carried out using conditional process analysis macro Model 21 on IBM SPSS. Results: Findings showed psychological empowerment having a large unconditional direct effect on job satisfaction (coeff = .80; p < .05); a significant effect of psychological empowerment on work engagement (coeff = .65; p < .05); a significant effect of personal resources on work engagement (coeff = .16; p < .05); a significant effect of work engagement on job satisfaction (coeff = .41; p < .05); and a significant effect of job resources on job satisfaction (coeff = .48; p < .05). The relationship between work engagement and job satisfaction was significantly but inversely moderated by job resources (coeff = -.01; p < .05). Conclusion: Personal resources will not moderate the relationship between psychological empowerment and work engagement, but job resources will inversely moderate between work engagement and job satisfaction